PENGARUH BUDAYA ORGANISASI DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA PEGAWAI DI DINAS KEPENDUDUKAN CATATAN SIPIL KABUPATEN BIMA - irvan kurniawan; Muhammad yusuf; Julaiha (Jurnal Nusa Manajemen, 2026)
This study aims to determine the influence of organizational culture and work environment on employee job satisfaction at the Population and Civil Registration Office of Bima Regency. The approach used in this study is an associative approach. The population in the study amounted to 69 people, with a sample of 38 ASN. Data collection techniques used were observation, questionnaires, and literature review. Data analysis techniques used were validity and reliability tests, classical assumption tests, multiple linear regression analysis, correlation coefficients, coefficients of determination, T-tests, and F-tests, processed using the Statistical Product and Service Solution (SPSS) version 20 program. The results of the study indicate that organizational culture (X1) and work environment (X2) simultaneously have a significant effect on employee job satisfaction at the Population and Civil Registration Office of Bima Regency.